THU0467-HPR A standardized educational program directed to patients for self-care promotion can be equally effective in patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), ankylosing spondylitis (AS). (23rd January 2014) - Cano-García, L.; Navas-Fernández, R.; Jiménez-Nuñez, F.G.; Ureña, I.; Manrique, S.; Romero-Barco, C.M.; Rodríguez-García, V.; Nieves-Martín, L.; Belmonte-Lόpez, M. Ά.; Coret, V.; Ordόñez, M.C.; Irigoyen, M.V.; et al.
Abstract : Objectives: To evaluate the results of a standardized educational intervention to improve the quality of life related to health (HRQL), physical function, adherence and pain perception in 3 diagnostic groups (RA, SLE, AS). Methods: Design: Uncontrolled open intervention. Patients: 30 RA (ACR criteria), 30 AS (ASAS criteria) and 23 SLE (ACR criteria) followed in the Rheumatology Service, HRUCH. Intervention: Training Group activity was provided by a nurse, an occupational therapist and a physiotherapist. The main topics were: (1) what is the AR/AE/SLE? (2) The treatment; (3) Promoting healthy behaviours and joint protection; (4) non-pharmacological management of pain; (5) Physical activity; and (6) Technical aids for daily living. Outcomes and variables: HRQL was assessed with EQ-5D and SF-36, the perception of pain and patient disease assessment with a VAS (0-100), physical function by HAQ for RA and SLE, HAQ-AS for AS, the adherence by Moriski-Green test, the chronic pain with chronic pain coping questionnaire (CAD-R). All variables ere collected before educational activity and after 3 months. Statistical analysis: Comparison between diagnostic groups of quantitative variables was performed by ANOVA one factor. Results: A total of 83 patients were studied: 30 with RA (83.3% women), 23 with SLE (100% women) and 30 with AS (33.3% women). The intervention improved the HRQL expressed as EQ-5D (p<0.001), EQ-5D health VAS (p<0.001) and mental component SF-36 (p=0.006). There was improvement in VAS pain (p=0.012), VAS disease (p=0.028) and CAD-R (p<0.001) also in all patients. Although there were no differences in CAD-R of diagnostic subgroups, a difference in VAS pain at baseline (p=0.019) and after 3 months (p=0.038) between AS and RA (p=0.044) was detected (in favour of AS). Patients with HAQ-AS post-intervention improved more than HAQ of SLE-patients (p<0.005). No differences for diagnosis were detected in Moriski-Green test. Conclusions: This standardized educational program directed to patients with AS, RA and SLE for self-care promotion produce an improvement quite homogeneous in all patients independent their diagnosis. Disclosure of Interest: None Declared